Evaluation of a CRISPR/Cas9 based gene editing system for Urochloa sp. (Poaceae) - Lopera Cardona, Mariana; Juanillo, Kevin; Marin, Didier; Chavarriaga Aguirre, Paul (2025)
The agricultural sector is a major contributor to greenhouse gas emissions, with livestock being a significant source of methane (CH₄) through enteric fermentation. As forage quality, digestibility, and composition directly influence CH₄ production in the rumen, the CRISPR/Cas9 technology offers a promising solution to tackle this problem by targeting these traits. Due to its agronomic and economic importance, the forage grass Urochloa Ruziziensis. has been selected for the development of a gene editing protocol using Agrobacterium-mediated transformation of embryogenic calli. The PDS (Phytoene Desaturase) gene has been selected as a proof of concept. The deactivation of this gene is expected to produce albino plants that will be easily identified in vitro. Simultaneously, two genes, Bmr6 and FatB, have been identified as candidates for improving digestibility and increasing production of anti-methanogenic compounds (AMCs) in this species. The Bmr6 gene encodes the enzyme cinnamyl alcohol dehydrogenase (CAD), which plays a critical role in the lignin biosynthesis pathway. Evidence shows that mutation of Bmr6 in sorghum results in reduced lignin content and increased cell wall digestibility, making fibers more accessible for livestock digestion. This leads to shorter fermentation times in the rumen, thereby reducing methane production, while improving feed intake and livestock productivity. In turn, the FatB gene encodes an acyl-ACP thioesterase involved in fatty acid biosynthesis. Silencing the FatB gene to reduce levels of saturated fatty acids can increase the availability of unsaturated fatty acids, altering ruminal fermentation pathways. This adjustment can create competition for hydrogen within the rumen, limiting the substrate available to methanogenic archaea, which use hydrogen to produce methane. Both genes have been identified in Urochloa Ruziziensis, and sgRNAs have been designed. These genetic modifications could significantly reduce methane emissions while enhancing the nutritional quality of animal products. As of now, all gene editing efforts and advances are also being supported by ongoing work to optimize Agrobacteirum-mediated genetic transformation and refine regeneration protocols, ensuring the successful implementation of the CRISPR/Cas9 technology in Urochloa sp.